Teaching Languages to Adolescent Learners From Theory to Practice - Erlam, Rosemary (Social Sciences, 2021)
Engaging and accessible, this book illustrates the principles of instructed language learning by presenting real life, practical examples from teachers. It illustrates best practice from high school classrooms, highlighting the needs of the adolescent language learner and making the case that adolescence is a prime time for language learning.